COVID-19 in unvaccinated patients with inborn errors of immunity—polish experience - Kołtan, Sylwia; Ziętkiewicz, Marcin; Grześk, Elżbieta; Becht, Rafał; Berdej-Szczot, Elżbieta; Cienkusz, Magdalena; Ewertowska, Marlena; Heropolitańska-Pliszka, Edyta; Krysiak, Natalia; Lewandowicz-Uszyńska, Aleksandra; Mach-Tomalska, Monika; Matyja-Bednarczyk, Aleksandra; et al. (Frontiers in Immunology, 2022)
At the beginning of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic, patients with inborn errors of immunity (IEI) appeared to be particularly vulnerable to a severe course of the disease. It quickly turned out that only some IEI groups are associated with a high risk of severe infection. However, data on the course of Coronavirus Disease 2019 (COVID-19) in patients with IEI are still insufficient, especially in children; hence, further analyses are required. The retrospective study included 155 unvaccinated people with IEI: 105 children and 50 adults (67.7% and 32.3%, respectively). Male patients dominated in the study group (94 people, 60.6%). At least two comorbidities were found in 50 patients (32.3%), significantly more often in adults (56% vs. 21%). Adult patients presented significantly more COVID-19 symptoms. Asymptomatic and mildly symptomatic course of COVID-19 was demonstrated in 74.8% of the entire group, significantly more often in children (88.6% vs. 46%). Moderate and severe courses dominated in adults (54% vs. 11.4%). Systemic antibiotic therapy was used the most frequently, especially in adults (60% vs. 14.3%). COVID-19-specific therapy was used almost exclusively in adults. In the whole group, complications occurred in 14.2% of patients, significantly more often in adults (30% vs. 6.7%). In the pediatric group, there were two cases (1.9%) of multisystem inflammatory syndrome in children. Deaths were reported only in the adult population and accounted for 3.9% of the entire study group. The death rate for all adults was 12%, 15.4% for adults diagnosed with common variable immunodeficiency, 12.5% for those with X-linked agammaglobulinemia, and 21.4% for patients with comorbidity. The results of our study imply that vaccinations against COVID-19 should be recommended both for children and adults with IEI. Postexposure prophylaxis and early antiviral and anti-SARS-CoV-2 antibody-based therapies should be considered in adults with IEI, especially in those with severe humoral immune deficiencies and comorbidity.